Formulation and evaluation of bioadhesive buccal drug delivery of repaglinide tablets - Patel, Dasharath M; Shah, Pratik M; Patel, Chhagan N (Asian Journal of Pharmaceutics (AJP), 2014)
The purpose of this research was to formulate and evaluate bioadhesive buccal tablets of repaglinide using HPMC K15M as a sustained release polymer, chitosan as a bioadhesive polymer and ethyl cellulose as an impermeable backing layer. The tablets were evaluated for weight variation, thickness, hardness, friability, surface pH, mucoadhesive strength, swelling index, in vitro drug release, ex vivo mucoadhesion time and ex vivo drug permeation. A 32 full factorial design was used in present study for optimization. Tablets containing HPMC K15M and chitosan in the ratio of 1:1 and lactose as a filler (F2) had the maximum percentage of in vitro drug release. The swelling index, friability and in vitro drug release was affected by type of filler as dicalcium phosphate (DCP) had good binding ability compared to lactose. The surface pH of all tablets was found to be satisfactory (between 6.26 and 7.01), close to neutral pH; hence buccal cavity irritation should not occur with these tablets. F2 batch was considered optimum based on good bioadhesive strength (17.83Â±0.51 gm) and maximum similarity factor (64.43).The drug release from optimum batch followed zero order kinetics with non-Fickian diffusion. Drug-excipients compatibility study showed no interaction between drug and excipients. Stability study of optimized formulation showed that tablets were stable at accelerated environment condition. Thus, buccal adhesive tablet of repaglinide could be an alternative route to bypass hepatic first pass metabolism and to improve bioavailability of repaglinide.